649. Cefiderocol in Treating Patients Confirmed with Gram-negative Infections in US Hospital During Jan 2020 - Jun 2021. (15th December 2022) - Cai, Bin; Zhou, Yun; Cooper, Andrew
Abstract: Background: Cefiderocol (CFDC) has a broad activity against Gram-negative (GN) pathogens. This study describes the usage of CFDC in US hospitals in patients with microbiology data during the initial phase of commercialization. Methods: This retrospective study included patients with laboratory-confirmed GN infections in US hospitals treated with CFDC consecutively for ≥3 days between March 2020 to June 2021, as captured by Premier Healthcare data. This study describes the clinical characteristics, microbiology profile, CFDC usage, and post-CFDC initiation 14-day and 28-day in-hospital all-cause mortality (IH-ACM). Index culture was defined as the last day that culture sample(s) was taken before CFDC initiation or the first day the culture sample(s) was taken after CFDC initiation if no microbiology data before CFDC use was available. Index pathogens were all pathogens identified from the index culture(s). The index culture site was where the index culture was taken. Results: A total 187 in-patients received ≥3 days CFDC and had ≥1 microbiological result(s). The clinical characteristics of the patients and index culture results are provided in Table 1 and Table 2. About 60% of patients had at least one positive respiratory culture. The most frequent pathogens from the index culture were Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Klebsiella pneumoniae, and Acinetobacter baumannii . Nearly 75% of patients had one index pathogen, and 91% with one culture site. Almost 30% of patients had either one pathogen identified in multiple culture sites, or multiple pathogens from ≥1 culture site. Crude 28-day IH-ACM for patients with any A. baumannii was 8.3% (95%CI: 0% -19.4%), any P. aeruginosa was 17.3% (95%CI: 9.9-24.8%), any S. maltophilia was 18.4%, ( 95%CI: 6.1%-44.0%) and any K. pneumoniae was 26.1% (95%CI: 8.1%-44.0%). Crude 28-day IH-ACM for patients with positive respiratory culture was five times higher in COVID patients than non-COVID patients. Conclusion: During the initial phase of CFDC availability, the most frequent pathogens treated using CFDC were non-fermenters, and the most frequent culture site was respiratory. IH-ACM appears to be affected by infection characteristics, especially COVID-19 status. Disclosures: Bin Cai, MD, PhD, Shionogi: Shionogi employee Yun Zhou, MS, Shionogi: Employee of CRO hired by Shionogi Andrew Cooper, PhD, Shionogi: Shionogi employee.